الخصائص السيكومترية لمقياس الوعي الفونولوجي لدى التلاميذ المعاقين فكريًا - عايدة احمد ابراهيم حمزة حمزة; عمرو رفعت; عبد الصبور منصور محمد سيد احمد; كريستين زاهر حنا (Maǧallaẗ Kulliyyaẗ Al-Tarbiyyaẗ - Ǧamiʿaẗ Būr Saʿīd, 2024)
هدفت الدراسة الحالية إلى التحقق من الخصائص السيكومترية لمقياس الوعي الفونولوجي لدى التلاميذ المعاقين فكريًا، من خلال تطبيقه على عينة قوامها(30) تلميذًا من المعاقين فكريًا تراوحت أعمارهم ما بين(6-9) أعوام، بمتوسط (7.63) وانحراف معياري(1.13) وتراوحت نسبة الذكاء بين (55- 75) بمتوسط حسابي (64.77) وانحراف معياري(4.12). وقد اعتمدت الباحثة على استخدام بعض مؤشرات الصدق والثبات والاتساق الداخلي(مثل: صدق المحكمين، والصدق الظاهري، والصدق التلازمي، وطريقة إعادة الاختبار، والتجزئة النصفية، ومعاملات الارتباط) وأظهرت النتائج أن المقياس يتمتع بدرجة مرضية من الصدق والثبات والاتساق الداخلي، وعليه فإن مقياس الوعي الفونولوجي لدى التلاميذ المعاقين فكريًا يتمتع بخصائص سيكومترية مناسبة تجعله صالحًا للتطبيق على التلاميذ المعاقين فكريًا.Abstract: The current study aimed to verify the psychometric properties of the phonological awareness scale for students with intellectual disabilities, by applying it to a sample of (30) students with intellectual disabilities, whose ages ranged between (6-9) years, with an average (7.63) and a standard deviation (1.13). The IQ ranged between (55-75), with an arithmetic mean (64.77) and a standard deviation (4.12). The researcher relied on the use of some indicators of validity, reliability, and internal consistency (such as: the validity of the arbitrators, apparent validity, collateral validity, method of re-testing, split midterms, and correlation coefficients). The results showed that the scale has a satisfactory degree of validity, stability, and internal consistency. Phonology for students with intellectual disabilities has appropriate psychometric characteristics that make it applicable to students with intellectual disabilities.